2021
DOI: 10.3390/healthcare9050512
|View full text |Cite
|
Sign up to set email alerts
|

The Experienced Benefits of the 17-Item Benefit Finding Scale in Chinese Colorectal Cancer Survivor and Spousal Caregiver Couples

Abstract: The specific aims of the present study were twofold: (i) to examine the psychometric properties of a Chinese version of the 17-item Benefit Finding Scale (BFS-C), and (ii) to explore the experienced benefits in colorectal cancer (CRC) survivors and their spousal caregivers (SCs). A total of 286 CRC survivors and SCs participated in the investigation, which assessed participant variables of demographic characteristics and benefit finding (BF). Statistical methods applied were confirmatory factor analysis (CFA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Similarly, research exploring benefit-finding in the lived experiences of Chinese cancer survivors and their family carers highlights the high correlation of benefit-finding between family members (Chen et al, 2021;Li et al, 2018). The findings emphasize the importance of developing health management plans involving all family members.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Similarly, research exploring benefit-finding in the lived experiences of Chinese cancer survivors and their family carers highlights the high correlation of benefit-finding between family members (Chen et al, 2021;Li et al, 2018). The findings emphasize the importance of developing health management plans involving all family members.…”
Section: Discussionmentioning
confidence: 86%
“…Recent savoring (benefit‐reminding) research found the frequency of benefit‐reminding increased when it was encouraged by significant others (Samios et al, 2020). Similarly, research exploring benefit‐finding in the lived experiences of Chinese cancer survivors and their family carers highlights the high correlation of benefit‐finding between family members (Chen et al, 2021; Li et al, 2018). The findings emphasize the importance of developing health management plans involving all family members.…”
Section: Discussionmentioning
confidence: 99%
“…All outcome measurement tools used in the “4Cs: CRC” program have been determined by other studies to be reliable and valid. 10 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 These outcome measures will be taken at baseline (T0), immediately after the last intervention (T1), three months after the program (T2), and six months after the program (T3). In addition, participants’ basic information (eg, demographic information) will be collected at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…All the scales used in this study have been translated into Chinese and have indicated reliability and validity in Chinese groups (Chen et al, 2021;Q. Li, Lin, et al, 2016;Q.…”
Section: Marital Satisfactionmentioning
confidence: 99%